An Analysis of Language Styles Used by the Main Characters in the Dialogues in Business Proposal Series - Simamora, Riris Mutiara Paulina; Sherina, Sherina (ppjbsip, 2022)
Language styles emerge as one of the sociolinguistics subfields that focus on the way people speak based on the formality scale of the social life that people have. This research, entitled